To find the product of \( (23g^2 - 6n)^2 \) and \( (2 - 6) \) using the area model, we need to identify the components of the expressions mentioned.
The expression \( (23g^2 - 6n)^2 \) can be expanded using the formula \( (a - b)^2 = a^2 - 2ab + b^2 \):
-
Calculate \( a^2 \) where \( a = 23g^2 \): \[ a^2 = (23g^2)^2 = 529g^4 \]
-
Calculate \( b^2 \) where \( b = 6n \): \[ b^2 = (6n)^2 = 36n^2 \]
-
Calculate \( 2ab \): \[ 2ab = 2 \cdot 23g^2 \cdot 6n = 276g^2n \]
So, \[ (23g^2 - 6n)^2 = 529g^4 - 276g^2n + 36n^2 \]
Next, for \( (2 - 6) \), since \( 2 - 6 \) simplifies to \(-4\), we can find the full expression:
Now, we will multiply this by \(-4\): \[ (23g^2 - 6n)^2 \cdot -4 = (-4)(529g^4 - 276g^2n + 36n^2) \]
Distributing \(-4\) gives:
-
For the term \( 529g^4 \): \[ -4 \cdot 529g^4 = -2116g^4 \]
-
For the term \( -276g^2n \): \[ -4 \cdot (-276g^2n) = 1104g^2n \]
-
For the term \( 36n^2 \): \[ -4 \cdot 36n^2 = -144n^2 \]
So, the final product in standard form is: \[ -2116g^4 + 1104g^2n - 144n^2 \]
Therefore, the partial products are:
- Partial product in the orange box: This will be \(-4 \cdot 529g^4 = -2116g^4\)
- Partial product in the blue box: This will be \(-4 \cdot (-276g^2n) = 1104g^2n\)
And the final product written in standard form is: \[ -2116g^4 + 1104g^2n - 144n^2 \]